Knit to be tied - Sefton, Maggie (Sefton, Maggie. Knitting mystery., 2016)
"The New York Times bestselling author of Purl Up and Die returns as Kelly Flynn and the Lambspun Knitters must come together before their whole town unravels. In Fort Connor, Colorado, the friends at the House of Lambspun knitting shop are welcoming a new face into the fold. Shy, sweet, and pregnant Nancy Marsted would like to knit a baby hat, and the Lambspun ladies are more than happy to show her the ropes. They share their own pregnancy yarns and soon learn the father of Nancy's baby isn't quite the man she dreamed he was. He's a cad. Then one dark night a speeding car fatally mows down the dad-to-be and strikes a cyclist, spinning the town into a frenzy. Everyone worries that a crazed killer is on the loose. Now it's up to Kelly and the gang to put down their needles and cut to the chase before the culprit is driven to kill again"--